Aligning Policy Design With Science to Achieve Food Security: The Contribution of Genome Editing to Sustainable Agriculture - Anyshchenko, Artem (Frontiers in Sustainable Food Systems, 2022)
The need to meet the food demands of the world's growing population is the main challenge to global agricultural policy and economy. Issues in food security require innovative solutions. Modern biotechnology has a significant potential to contribute to food security, wealth, and sustainable development. Genetic engineering offers tools to improve nutrition, increase yield, and enhance crop resilience. New techniques of genome editing provide ample means to overcome limitations inherent in conventional plant breeding, but their industrial applicability depends on regulatory environment, decision making, and public perception. An alignment of goals between science and policy can help realise the potential of modern biotechnology to contribute to food security, wealth, and sustainable development.